INTERPRETASI KONDISIAIR BAWAH TANAH STUDI KASUS DI KECAMATAN TENAYAN RAYA KOTA PEKANBARU DENGAN MENGGUNAKAN METODE PUMPING TEST - Awaludin Rakhmat; Juandi Muhammad; Usman Malik (Universitas Riau, 2019)
The purpose of the research on the potential of underground water in ring wells in the District of Tenayan Raya Pekanbaru City using the experimental method of pumping test is to determine the potential of underground water, and determine the value of transmissivity so that it can be known the feasibility of well water for surrounding communities. Data was taken on 30 ring wells in Tenayan Raya District, Pekanbaru City. The results obtained are wells that have the lowest potential for underground water in Kadiran Street, Kulim Village with a value of drawdown is 2.1610 m. Wherea the highest potential as good underground water is in the well at Gunung Kidul Street, Tangkerang Timur Village with value of drawdown is 2.0407 m. This ring well has the potential of underground water which is likely to provide water for a long time. The transmissivity obtained from the 30 ring wells is 10.7684 m2 / day. This value shows good groundwater quality and has the potential to meet the needs of residential areas.